If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + x = 26 Solving -2 + x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 26 + 2 Combine like terms: -2 + 2 = 0 0 + x = 26 + 2 x = 26 + 2 Combine like terms: 26 + 2 = 28 x = 28 Simplifying x = 28
| 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 | | -11=x+4 | | 3x^2y+6x^2y^2-144xy^3= | | x^2-3x=-8 | | x=4+-3y | | x^2-18+77= | | 4(2x+-1)=27+3(2x-5) | | x(x+3)=18 | | 38=25+2y | | 7p=6p^2-3 | | v^2-6v+15= | | 0=-16t^2+35t+8 | | 1-5x^2=-3x | | 3(q+4)-10q=2q+3 | | 2x+3x+5=5(2x-3) | | 4z-2(z+6)=7z+8 | | 5x^2-30x-80= | | 6y+2y=9-3y | | 2x-5x=5+4y | | 5x-x+7x= | | 3x+2=5-x | | 2x=3x-2 | | 502.4=12(3.141592654)(r)+(3.141592654)(r^2) |